2021
DOI: 10.47815/apsr.2021.10079
|View full text |Cite
|
Sign up to set email alerts
|

Soil test based fertilizer prescriptions under integrated plant nutrient management system for carrot in an Inceptisol

Abstract: A field experiment was conducted at Agricultural Research Farm, Banaras Hindu University, Varanasi in an Inceptisol during rabi 2020-21 to develop a targeted yield equation for carrot crop. After developing three levels of fertility gradient with respect to available NPK in soil, the main experiment was conducted by taking carrot as a test crop. Initial soil data, carrot yield and NPK uptake by carrot crop were used for obtaining four important basic parameters, viz., nutrients required to produce a quintal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(3 reference statements)
3
1
0
Order By: Relevance
“…This may be due to the release of soil potassium from the native source which resulted in the higher uptake of K from soil source by the crop. Similar result was also reported by Singh et al (2021). Targeted yield equations for cucumber (cv.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This may be due to the release of soil potassium from the native source which resulted in the higher uptake of K from soil source by the crop. Similar result was also reported by Singh et al (2021). Targeted yield equations for cucumber (cv.…”
Section: Resultssupporting
confidence: 90%
“…These equations may be useful in red, laterite and yellow soils (Inceptisols and Alfisols). Similar study and results were also reported by various workers in different crops like carrot (Singh et al, 2021) and Finger millet (Ayushi et al, 2022). Targeted yield approach may be advantageous for balanced fertilization on crop taking into account of the soil available nutrient status and the crop need.…”
Section: Resultssupporting
confidence: 86%
“…A higher yield was recorded in STCR-IPNS than in STCR-NPK alone. This finding was in accordance with the results given for Pigeon-pea [6] and pea [15]. This specified superiority of STCR-IPNS over STCR-NPK alone was also reported by [16].The lowest grain yield recorded in NPK alone treatments might be due to the solo application of NPK fertilizer requiring some additional essential nutrients that would be available in organic manures [17].…”
Section: Grain Yieldsupporting
confidence: 92%
“…Similar finding was recorded by Shukla et al [19]. According to Singh et al [20], the integrated usage of inorganic + organic fertiliser combined with biofertilizers (Azotobacter + PSB) considerably boosted cane production. Lakshmi et al [21] explained that FYM + RDF recorded a higher cane yield than RDF alone.…”
Section: Yield Attributes and Yieldsupporting
confidence: 86%
“…According to Thakur et al [24], cane juice quality, including brix, sucrose, and purity content, is unchanged by the use of organic and conventional farming methods. According to research by Sinha et al [20] and Kumar [25], both organic and inorganic nutrients had no impact on the juice's quality indicators of brix, pol, and purity.…”
Section: Juice Qualitymentioning
confidence: 99%